2016
DOI: 10.1515/acs-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the growth of Lactobacillus plantarum in milk in dependence on temperature

Abstract: The effect of temperature on the growth dynamics ofLactobacillus plantarumin the model environment of UHT milk was investigated. Based on the experiments between temperatures ranged from 8 to 40 °C, growth dynamics of the studied isolate was positively determined by the cultivation temperature that led to increasing intensity of growth in the exponential phase (except for temperatures 38 and 40 °C). Final counts in stationary phase have reached concentrations about 107CFU · ml−1from initial 103CFU · ml−1, exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 17 publications
3
20
0
1
Order By: Relevance
“…Most probiotic bacteria grow slowly in milk and the rate of acid production is usually too slow to support an adequate fermentation process (Shah, ). Matejčeková, Liptáková, Spodniaková, and Valík () reported that during growth of Lb. plantarum no significant changes in pH values were recorded in comparison to the initial state (0.00 to 0.24).…”
Section: Resultsmentioning
confidence: 99%
“…Most probiotic bacteria grow slowly in milk and the rate of acid production is usually too slow to support an adequate fermentation process (Shah, ). Matejčeková, Liptáková, Spodniaková, and Valík () reported that during growth of Lb. plantarum no significant changes in pH values were recorded in comparison to the initial state (0.00 to 0.24).…”
Section: Resultsmentioning
confidence: 99%
“…acidophilus NCFM Howaru [25] or Lb. plantarum [26] strong influence of temperature on the final number of bacterial cells was observed. The cause might be Fresco being a mixed culture, since Champagne et al [27] noticed about 20% increase in growth of cells and about 13% higher growth dynamics of Lc.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this fact, the growth and acid production of probiotic bacteria in milk is usually too slow to support an adequate fermentation process [9]. Matejčeková et al [31] reported no significant changes in active acidity (0.00-0.24 units) in the L. plantarum HM1 strain during growth and multiplication in milk. Negligible acid production was also recorded in a study of Valík et al [32] in L. rhamnosus GG in milk.…”
Section: Resultsmentioning
confidence: 99%